Surgical Predictors of Clinical Outcome Six Years following Revision ACL Reconstruction. Issue 7 (30th July 2021) - ,; Wright, Rick; Wright, Rick
Objectives: Revision ACL reconstruction has been documented to have inferior outcomes compared with primary ACL reconstructions. The reasons why remain unknown. The purpose of this study was to determine if surgical factors performed at the time of revision ACL reconstruction have the ability to influence a patient's outcome at 6-year follow-up. Methods: Revision ACL reconstruction patients were identified and prospectively enrolled between 2006 and 2011. Data collected included baseline demographics, surgical technique and pathology, and a series of validated patient-reported outcome instruments (IKDC, KOOS, WOMAC, and Marx activity rating score). Patients were followed up for 6 years and asked to complete the identical set of outcome instruments. Regression analysis was used to control for age, gender, BMI, activity level, baseline outcome scores, revision number, time since last ACL reconstruction, and a variety of surgical variables, in order to assess the surgical risk factors for clinical outcomes 6 years after revision ACL reconstruction. Results: 1234 patients met the inclusion criteria and were successfully enrolled. 716 (58%) were males, with a median cohort age of 26 years. The median time since their last ACL reconstruction was 3.3 years. At 6 years, follow-up was obtained on 77% (949/1234). Several surgical factors at the time of revision surgery were found to be significant drivers of poorer outcomes at 6 years. The most consistent surgical variables driving outcome in revision patients were related to femoral and tibial fixation. Using an interference screw for femoral fixation compared with a cross-pin resulted in significantly better outcomes in 6-year IKDC scores (OR=2.2; 95% CI=1.2, 3.8; p=0.008), KOOS sports/rec and KOOS QOL subscales (OR range = 2.2-2.7; 95% CI=1.2, 3.8; p< 0.001). Using an interference screw compared with a cross-pin also resulted in 2.6 times less likely to have a subsequent surgery within the 6 years. Using an interference screw for tibial fixation compared to any combination of tibial fixation techniques also resulted in significantly improved IKDC (OR=2.0; 95% CI=1.3, 2.9; p=0.001), KOOS pain, ADL, sports/rec (OR range=1.5-1.6; 95% CI=1.0, 2.4; p<0.05) and WOMAC pain and stiffness subscales (OR range=1.5-1.8; 95% CI=1.0, 2.9; p<0.05). Using a transtibial surgical approach compared to an anteromedial portal approach resulted in significantly improved KOOS pain and QOL subscales at 6 years (OR=1.5; 95% CI=1.02, 2.2; p<0.04). Avoiding a notchplasty significantly improved 2 year outcomes of the IKDC (OR=1.5; 95% CI=1.1, 2.0; p=0.013), KOOS ADL and QOL subscales (OR range= 1.4; 95% CI=1.0, 1.9; p< 0.04), and the WOMAC stiffness and ADL subscales (OR range = 1.4-1.5; 95% CI=1.0, 2.1; p< 0.04). Regarding tunnel position at the time of the revision surgery, surgeons who noted that the tibial tunnel aperture position was in the 'optimum position' fared significantly worse in 6-year IKDC scores (OR=0.6; 95% CI=0.4, 0.8; p=0.003), Marx activity levels (OR=0.20; 95% CI=0.07, 0.6; p=0.005), KOOS symptoms, pain, sports/rec, and QOL subscales (OR range=0.56-0.68; 95% CI=0.38, 0.47; p< 0.05), compared with surgeons who opted for either a blended new tunnel or noted that the previous tunnel had the same tunnel aperture, but 'compromised position'. Lower baseline outcome scores, lower baseline activity level, being a smoker at the time of the revision, higher BMI, female gender, shorter time since the patient's last ACL reconstruction, and having a previous ACL reconstruction on the contralateral side all significantly increased the odds of reporting poorer clinical outcomes at 6 years. Knee flexion angle at the time of graft fixation and biologic enhancement (i.e. PRP) did not influence 6-year outcomes in this revision cohort. Conclusions: There are surgical variables that the physician can control at the time of an ACL revision which have the ability to modify clinical outcomes. Based on outcomes at 6 years, opting for a transtibial surgical approach, choosing an inference screw for femoral and tibial fixation, and not performing a notchplasty will improve the patient's odds of having a significantly better 6-year clinical outcome. :